No Ordinary Mainstream Illness: How HIV Doctors Perceive the Virus. (January 2014) - Persson, Asha; Newman, Christy E.; Hopwood, Max; Kidd, Michael R.; Canavan, Peter G.; Kippax, Susan C.; Reynolds, Robert H.; de Wit, John B. F.
Research has shown that social representations of HIV can constitute barriers to health workers' willingness to provide HIV care. Considering a growing shortage in the HIV primary workforce in Western countries, we examine how HIV is perceived today by doctors involved in its care. In 1989 Sontag predicted that once the virus became better understood and treatable, the dehumanizing meanings that defined the early epidemic would vanish and HIV would turn into an ordinary illness. However, research shows that HIV still carries stigma, including in the health care sector. Drawing on qualitative interviews, we found that HIV doctors in Australia perceived HIV as a far-from-ordinary chronic illness because of its extraordinary history and its capacity to extend in multiple clinical and social directions. These rarely explored perspectives can contribute to the social reframing of HIV and to strategies to build a dedicated HIV workforce in Australia and elsewhere.